Reinvestigation of unidentified causative variants in FXI‐deficient patients: Focus on gene segment deletions. Issue 1 (4th October 2022) - De Mazancourt, Philippe; Harroche, Annie; Pouymayou, Katia; Sigaud, Marianne; Falaise, Céline; Stieltjes, Natalie; Castet, Sabine‐Marie; Tardy, Brigitte; Zawadzki, Christophe; Goudemand, Jenny; Dargaud, Yesim
Abstract: Introduction: Data on failure to identify the molecular mechanism underlying FXI deficiency by Sanger analysis and the contribution of gene segment deletions are almost inexistent. Aims and methods: Prospective and retrospective analysis was conducted on FXI‐deficient patients' DNA via Next Generation Sequencing (NGS), or Sanger sequencing and Multiplex Probe Ligation‐dependent Assay (MLPA) to detect cryptic causative gene variants or gene segment deletions. Results: Sanger analysis or NGS enabled us to identify six severe and one partial (median activity 41 IU/dl) FXI deficient index cases with deletions encompassing exons 11–15, the whole gene, or both. After Sanger sequencing, retrospective evaluation using MLPA detected seven additional deletion cases in apparently homozygous cases in non‐consanguineous families, or in previously unsolved FXI‐deficiency cases. Among the 504 index cases with a complete genetic investigation (Sanger/MLPA, or NGS), 23 remained unsolved (no abnormality found [ n = 14] or rare intronic variants currently under investigation, [ n = 9]). In the 481 solved cases (95% efficiency), we identified F11 gene‐deleted patients (14 cases; 2.9%). Among these, whole gene deletion accounted for four heterozygous cases, exons 11–15 deletion for five heterozygous and three homozygous ones, while compound heterozygous deletion and isolated exon 12 deletion accounted for one case each. Conclusion: Given the high incidence of deletions in our population (2.9%), MLPA (or NGS with a reliable bioinformatic pipeline) should be systematically performed for unsolved FXI deficiencies or apparently homozygous cases in non‐consanguineous families.